Collaborating with cardiac sonographers to develop work-related musculoskeletal disorder interventions. Issue 9 (1st September 2016) - Sommerich, Carolyn M.; Lavender, Steven A.; Evans, Kevin; Sanders, Elizabeth; Joines, Sharon; Lamar, Sabrina; Radin Umar, Radin Zaid; Yen, Wei-Ting; Li, Jing; Nagavarapu, Shasank; Dickerson, Jennifer A.
Abstract: For more than two decades, surveys of imaging technologists, including cardiac sonographers, diagnostic medical sonographers and vascular technologists, have consistently reported high prevalence of work-related musculoskeletal discomfort (WRMSD). Yet, intervention research involving sonographers is limited. In this study, we used a participatory approach to identifying needs and opportunities for developing interventions to reduce sonographers' exposures to WRMSD risk factors. In this paper, we present some of those needs. We include descriptions of two interventions, targeted for cardiac sonographers, that were developed, through an iterative process, into functional prototypes that were evaluated in pilot tests by practicing sonographers. One of these interventions is now in daily use. We would like other engineers and ergonomists to recognise this area of opportunity to apply their knowledge of biomechanics and design in order to begin to address the high prevalence of WRMSDs in sonographers, by working with sonographers to develop useful and usable interventions. Practitioner Summary : This paper discusses needs, opportunities and methods for working with sonographers in order to develop interventions to reduce their exposure to risk factors for work-related musculoskeletal discomfort. Results from field tests of two novel interventions targeting cardiac sonographers are also presented.